Synthesis and research of new superacid ZrO2— SiO2—SnO2 oxide - Prudius, S.V.; Hes, N.L.; Trachevskiy, V.V.; Brei, V.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The superacid ternary ZrO2—SiO2—SnO2 oxide has been synthesized by the sol-gel method with different atomic ratios Zr : Si : Sn. It is determined that superacid sites are formed at the ion content: 10 ⩽ Zr4+ ⩽ 35, 50 ⩽ Si4+ ⩽ 53, 5 ⩽ Sn4+ ⩽ 40 %. The highest strength of acid sites (H0 = –14.52) is observed in the interval: 21 ⩽ Zr4+ ⩽ 29, 60 ⩽ Si4+ ⩽ 67, 11 ⩽ Sn4+ ⩽ 20 %. According to the acid sites strength distribution on Zr29Si60Sn11 surface, there are 10 % of superacid sites (−14.52 ⩽ H0 ⩽ −12.14) and 40 % of strongly acid sites with −12.14 ⩽ H0 ⩽ −8.2 at the total acidity of 1.5 mmol/g. The total concentration of acid sites on ZrO2—SiO2—SnO2 surface is 1.1–1.7 mmol/g. All samples are characterized by a highly developed surface (200–400 m2/g) and an average pore diameter of ≈ 3 nm. Samples with Sn ⩽ 25 and Zr ⩽ 45 % have amorphous structure. It is shown that, at the tin content up to 25 % (at.), SnO4 and SnO6 species are observed in the structure of ZrO2—SiO2—SnO2. At increasing the tin content, the formation of SnO2 is observed. From the electron diffuse reflectance spectra of ZrO2—SiO2— SnO2 samples, the limiting band gap of 3.8–4.3 eV is calculated, that is a criterion of the synthesis of superacid ZrO2—SiO2—SnO2. According to the 119Sn and 29Si MAS NMR spectra of ZrO2—SiO2—SnO2, a partial shift of the electron density from zirconium atoms to silicon and tin atoms is observed that causes the formation of supera cid Lewis sites (H0 = −14.52). It is shown that superacid Zr29Si60Sn11 catalyst efficiently catalyzes the acy lation of toluene with acetic anhydride at 150 °С in a flow reactor with 45 % conversion of anhydride at 100 % selectivity towards n-methylacetophenone.